PENGEMBANGAN KEMAMPUAN MOTORIK KASAR MELALUI PERMAINAN BOLA KECIL TRADISIONAL PADA ANAK USIA 5-6 TAHUN DI TK PAUD PERBATASAN BATARKUSU FURSUY - Tobarat, Mistalis; Lokolo, L. J.; Abarua, H. (Inovasi Pembangunan : Jurnal Kelitbangan, 2018)
The development of gross motor skills in early childhood is crucial as it involves the brain, nerves, and large muscles, starting from infancy to age 6. Appropriate motor stimulation, such as playing catch, enhances children's gross motor skills. Parents play a crucial role in providing this stimulation, influencing their social skills. Early childhood educators need to understand the characteristics of 5-6-year-old children's gross motor skills to design suitable activities. Traditional games, like playing with small balls, are effective in improving gross motor skills. This research aims to provide recommendations for educators and parents to support children's physical development through enjoyable games. The research method refers to systematic steps in obtaining scientific knowledge. This study employs the PTK approach, involving planning, action, observation, and reflection stages. It was conducted in TK PAUD Perbatasan Batarkusu Fursuy for one month with 20 students aged 5-6. Observation techniques were used to gather data on gross motor development and playing catch. The results were analyzed descriptively and qualitatively to assess the effectiveness of the game in developing children's motor skills. Playing catch plays a significant role in the development of gross motor skills in children at PAUD Perbatasan Batarkusu Fursuy. Cycle I shows development, while Cycle II shows significant improvement. The importance of integrating play activities in early childhood education is emphasized.